The Effect of Work Engagement and Burnout to Retail Employee Performance - Hanifah Siti Sarah; Eryandra, Alvin (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
The purpose of this study was to determine how work engagement and burnout affect the performance of retail employees in this study using quantitative research methods, with a total of 350 respondents who are store employees of one of the retail organizations in Jabodetabek. Data collection is done offline by distributing questionnaires and using online methods via google form. The data analysis process uses Jamovi 2.4 software and uses multiple linear regression analysis methods. Based on the research results, it is known that (1) Work engagement has no effect on employee performance, (2) Burnout has a positive effect on employee performance, (3) Work engagement and burnout positively affect employee performance by 31.5%.